The Effect of Interest Rates and Inflation on Stock Prices in Banking Company KBMI 4 Listed on the Indonesia Stock Exchange - Pradana, I Dewa Gede Kartika Yudha; Santini, Ni Made; Suriani, Ni Nyoman (Journal of Governance, Taxation and Auditing, 2026)
This research was conducted based on the inconsistency of previous research results regarding the phenomenon of stock price fluctuations due to changes in interest rates and inflation. This study aims to analyze and obtain empirical evidence related to the effect of interest rates and inflation on stock prices in KBMI 4 category banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The study uses secondary time series data taken from the official websites of Bank Indonesia and the Indonesia Stock Exchange. The sampling technique used is saturation sampling or total sampling. The research sample is all banking companies included in the KBMI 4 category that are listed on the Indonesia Stock Exchange for the 2019-2023 period with a total of 4 issuers. The data analysis technique used is multiple linear regression analysis and the data is processed with the SPSS 25 data processing application. The test results show that simultaneously there is a positive and significant influence between interest rates and inflation on stock prices. Partial testing found that interest rates have an insignificant effect on stock prices, while inflation has a positive and significant effect on stock prices.